2019
DOI: 10.3390/su11143842
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital, Profitability, and Productivity: Evidence from Pakistani Financial Institutions

Abstract: The idiosyncratic and knowledge-intense nature of the financial institutions requires them to rely more on intangible than on tangible resources. Over the past two decades, researchers have been motivated to embark on the relationship between intellectual capital (IC) and performance of financial institutions. Considering the knowledge-based intellect as a critical skill of this era, the current study examines the impact of IC on the performance of 111 Pakistani financial institutions (PFIs) over the period 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 87 publications
8
61
0
2
Order By: Relevance
“…However, a study in Taiwan by Shiu [65] showed a negative relationship between IC and productivity of listed technological firms. Yao et al [66] found an inverted U-shaped relationship between IC and the productivity of Pakistani financial institutions. In addition, Pal and Soriya [67] confirmed that IC has no significant impact on companies' productivity in Indian pharmaceutical and textile industry.…”
Section: Ic and Firm Performancementioning
confidence: 99%
See 4 more Smart Citations
“…However, a study in Taiwan by Shiu [65] showed a negative relationship between IC and productivity of listed technological firms. Yao et al [66] found an inverted U-shaped relationship between IC and the productivity of Pakistani financial institutions. In addition, Pal and Soriya [67] confirmed that IC has no significant impact on companies' productivity in Indian pharmaceutical and textile industry.…”
Section: Ic and Firm Performancementioning
confidence: 99%
“…Thus, the existence of persist profitability, unobserved heterogeneity, and endogeneity makes the results of OLS methods inconsistent and biased. Therefore, for the robustness of our results, we followed Haris et al [20] and Yao et al [66] and applied two-step GMM system estimator, which is efficient and deals with performance persistence, unobserved heterogeneity, serial correlation, and endogeneity, thus, produces robust and unbiased results.…”
Section: Robustness Checkmentioning
confidence: 99%
See 3 more Smart Citations